2001
DOI: 10.1128/cdli.8.6.1164-1170.2001
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Interleukin-10, Tumor Necrosis Factor Alpha, and Erythropoietin Levels among Children with Acute, UncomplicatedPlasmodium falciparumMalaria

Abstract: Anemia is an important complication of malaria, and its pathogenesis is not well understood. To gain insight into potential age-related relationships between tumor necrosis factor alpha (TNF-␣), interleukin 10 (IL-10), erythropoietin, and anemia during acute malaria, 273 children of ages 12 to 120 months presenting with acute, uncomplicated malaria in Kampala, Uganda, were monitored at enrollment and 3 and 7 days later. Younger children had higher geometric mean erythropoietin, TNF-␣, and ␣ 1 -acid glycoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 35 publications
3
44
1
1
Order By: Relevance
“…However, in contrast, IL-10 has been shown to downregulate the expression of TNF-a by human monocytes , an effect that might be expected to inhibit the suppression of erythropoiesis by TNF-a. Among children with acute malaria, a high ratio of IL-10 to TNF-a is associated with milder anemia (Othoro et al, 1999;Nussenblatt et al, 2001). In contrast, with the present study, which did not involve children with malaria, children with iron deficiency seemed to have a higher IL-10/TNF-a ratio than children without iron deficiency.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, in contrast, IL-10 has been shown to downregulate the expression of TNF-a by human monocytes , an effect that might be expected to inhibit the suppression of erythropoiesis by TNF-a. Among children with acute malaria, a high ratio of IL-10 to TNF-a is associated with milder anemia (Othoro et al, 1999;Nussenblatt et al, 2001). In contrast, with the present study, which did not involve children with malaria, children with iron deficiency seemed to have a higher IL-10/TNF-a ratio than children without iron deficiency.…”
Section: Discussioncontrasting
confidence: 81%
“…A stronger association between elevated TNF-a and/or elevated AGP and anemia Vitamin A deficiency, iron deficiency, and inflammation to anemia MV Gamble et al might be found among ill children drawn from a clinic or hospital-based study, where the anemia of chronic disease would be more common. Elevations of serum TNF-a and/or AGP can occur in the presence of infection, such as malaria (Nussenblatt et al, 2001), diarrheal disease (Azim et al, 1999), or acute lower respiratory infection . This study was limited in that other acute-phase response proteins, such as C-reactive protein, were not measured, and it is possible that a combination of elevated AGP and/or elevated C-reactive protein would have detected a greater proportion of children with inflammation than AGP alone.…”
Section: Discussionmentioning
confidence: 99%
“…104,105 However, several studies of malaria in African children suffering from malarial anemia have shown appropriately raised Epo concentrations. 25,[106][107][108] In fact, the Epo levels in malarial anemia are more than 3-fold higher when compared with anemic children without malaria. 72 It is possible that ineffective or inadequate Epo synthesis does contribute to malarial anemia in some settings, possibly related to age, ethnic origin, or presentation of the patient.…”
Section: Org Frommentioning
confidence: 99%
“…Previous hematological studies of individuals with malaria illustrate that bone marrow abnormalities, such as ineffective erythropoiesis, dyserythropoiesis, and reduced erythroblast proliferative rates, contribute to the development of severe anemia (1,12,42,49). Moreover, P. falciparum malaria is defined by a suboptimal reticulocyte response for the degree of anemia, even under conditions in which there are adequate levels of erythropoietin, a critical stimulus for erythropoiesis (25,32). Our previous results in western Kenya showing that children with SMA have a reduced erythropoietic response (RPI) are consistent with these findings (46).…”
Section: Figmentioning
confidence: 99%